art education, gender equality, gender stereotypes, inclusivity - Firmadhani, Annisa' Ayu; Sugiarto, Eko (Catharsis, 2025)
Fine arts education has an important role in supporting gender equality through the development of creativity, critical thinking, and empathy. However, challenges such as gender stereotypes, discrimination, and underrepresentation of women in the arts remain significant obstacles. This article aims to explore the role of art education in creating gender equality by identifying existing problems and opportunities. A conceptual approach is used by analysing literature related to gender-responsive art education and the UNESCO 2024 framework. The results of the analysis show that fine arts education can be a strategic tool to overcome gender stereotypes, increase women's participation, and create inclusive learning environments. In addition, gender-based programmes, such as inclusive curricula and cross-gender collaboration, can open wider access for women to work in the arts. Through equitable and inclusive art education, it is hoped to create a more equal society that respects gender diversity. The findings of this article emphasise the importance of using the UNESCO 2024 framework to create a more equitable and sustainable arts education system.